Star-like poly(peptoid)s with selective antibacterial activity. Issue 5 (11th January 2022) - Salas-Ambrosio, Pedro; Tronnet, Antoine; Badreldin, Mostafa; Reyes, Luzangel; Since, Marc; Bourgeade-Delmas, Sandra; Dupuy, Bruno; Verhaeghe, Pierre; Bonduelle, Colin
Abstract : We developed new macromolecular engineering approaches enabling the preparation of star-shaped and antimicrobial polypeptoids by ring-opening polymerization. Abstract : We developed new macromolecular engineering approaches enabling the preparation of star-like polypeptoids by ring-opening polymerization. Parallely to the evaluation of their cytotoxicity of the HepG2 human cell line, their screening toward a wide variety of Gram-positive and Gram-negative bacteria higlighted several compounds showing not only good but also selective antimicrobial activity.